Mild mitochondrial uncoupling induces HSL/ATGL‐independent lipolysis relying on a form of autophagy in 3T3‐L1 adipocytes. Issue 2 (15th June 2017) - Demine, Stéphane; Tejerina, Silvia; Bihin, Benoît; Thiry, Marc; Reddy, Nagabushana; Renard, Patricia; Raes, Martine; Jadot, Michel; Arnould, Thierry
Abstract : Obesity is characterized by an excessive triacylglycerol accumulation in white adipocytes. Various mechanisms allowing the tight regulation of triacylglycerol storage and mobilization by lipid droplet‐associated proteins as well as lipolytic enzymes have been identified. Increasing energy expenditure by inducing a mild uncoupling of mitochondria in adipocytes might represent a putative interesting anti‐obesity strategy as it reduces the adipose tissue triacylglycerol content (limiting alterations caused by cell hypertrophy) by stimulating lipolysis through yet unknown mechanisms, limiting the adverse effects of adipocyte hypertrophy. Herein, the molecular mechanisms involved in lipolysis induced by a mild uncoupling of mitochondria in white 3T3‐L1 adipocytes were characterized. Mitochondrial uncoupling‐induced lipolysis was found to be independent from canonical pathways that involve lipolytic enzymes such as HSL and ATGL. Finally, enhanced lipolysis in response to mitochondrial uncoupling relies on a form of autophagy as lipid droplets are captured by endolysosomal vesicles. This new mechanism of triacylglycerol breakdown in adipocytes exposed to mild uncoupling provides new insights on the biology of adipocytes dealing with mitochondria forced to dissipate energy. Abstract : The enhanced lipolysis observed in 3T3‐L1 adipocytes in response to mitochondrial uncoupling relies on a form of autophagy (and not HSL/ATGL) as lipid droplets are captured by endolysosomal vesicles. This is a new mechanism of triacylglycerol breakdown in adipocytes exposed to mild uncoupling that provides new insights on the biology of adipocytes dealing with mitochondria forced to dissipate energy.